Microservices migration patterns. (24th July 2018) - Balalaie, Armin; Heydarnoori, Abbas; Jamshidi, Pooyan; Tamburri, Damian A.; Lynn, Theo
Summary: Microservices architectures are becoming the defacto standard for building continuously deployed systems. At the same time, there is a substantial growth in the demand for migrating on‐premise legacy applications to the cloud. In this context, organizations tend to migrate their traditional architectures into cloud‐native architectures using microservices. This article reports a set of migration and rearchitecting design patterns that we have empirically identified and collected from industrial‐scale software migration projects. These migration patterns can help information technology organizations plan their migration projects toward microservices more efficiently and effectively. In addition, the proposed patterns facilitate the definition of migration plans by pattern composition. Qualitative empirical research is used to evaluate the validity of the proposed patterns. Our findings suggest that the proposed patterns are evident in other architectural refactoring and migration projects and strong candidates for effective patterns in system migrations.